Evaluation of the employment and integration strategies of persons with disabilities in Limpopo Department of Agriculture. - Komana, Sekepe Michael (My University, 2006)
Introduction: Discrimination against people with disabilities is evident in the social and economic environment. The categories of disabilities that are mostly affected by discrimination are physical, visual, hearing and mental impairment. Aim: The study was aimed at evaluating the employment and integration strategies of persons with disabilities in the Limpopo Department of Agriculture. This was done by evaluating the recruitment and employment methods of persons with disabilities; investigating the level of participation of persons with disabilities in the departmental activities and by evaluating the accessibility of the work environment. Method: The study was a descriptive, quantitative survey design. It described the perceptions of top management and senior management officials on the integration and employment of persons with disabilities into the mainstream of government activities. It described the available integration strategies and policies in the department as well as the physically accessible structures and environment to persons with disabilities. Out of a total of 33 senior managers that were surveyed in this study, only 18 responded. Results: The study revealed negative attitudes and perceptions in the department towards people with disabilities. Persons with physical impairment seem to be the most easily employed at a higher rate than other categories such as the visually impaired and the deaf, this was mainly influenced by the accessibility of adverts. On the other hand, a significant measure appeared to be in place to redress the imbalances in terms of gender. Conclusion: There was a general agreement that the method of recruitment was discriminatory against visual and hearing-impaired people, and therefore Managers must spearhead transformation and equity in their respective branches/sub- branches.
Thesis (MPA) --University of Limpopo, 2006
Keywords: Disabled employment opportunities; Handicapped -- Employment -- South Africa